The changing context of Jews in American Politics – 1930s to the Trump Era - Lazin, Fred (Chrześcijaństwo-Świat-Polityka, 2019)
The aim of the article is to show how the status of Jews in America changed from the 1930s to the present. The presented analyses focus on American politics regarding Jewish immigration to the USA, the attitude of American socjety and political authorities towards Jews, and the influence of Jewish organizations on American politics. The author distinguishes three periods characterized by different status of the Jews in the USA. The conclusion from the conducted analyses is the thesis that Jews in the USA went from an ethnic and religious minority, who was on the margins of society and politics to being an influential and mainstream actor in American politics.